Pengujian Performa, Tingkat Stres, dan Keamanan Pada Seluruh Website PPID Kabupaten Buleleng - Putu Surya Ardi Bhuana; I Made Edy Listartha; Gede Arna Jude Saskara (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology has encouraged local governments to provide digital-based public services through official websites. One of these services is the website of the Information and Documentation Management Officer (PPID) of Buleleng Regency which functions as a medium for transparency and public interaction. However, until now there has been no comprehensive testing of the performance, stress levels, and security of all PPID websites in the district. This study aims to evaluate performance, measure stress levels, and identify security gaps on 26 PPID Implementing websites connected to the Main PPID of Buleleng Regency. The method used in this study is Action Research, with testing carried out using three main tools, namely GTmetrix for performance, K6.io for stress testing, and Owasp Zap Scan for security. The test results showed that several websites experienced loading delays, slow server responses during high loads, and security gaps related to SSL and DNS were found. Recommendations for improvement are focused on optimizing performance, increasing server capacity, and tighter security configurations. This study contributes to improving the quality of public information services and supports the realization of a transparent, efficient, and secure government.